PENGARUH LATIHAN MENENDANG SEMBILAN BOLA KE GAWANG TERHADAP KEMAMPUAN SHOOTING PEMAIN SSB U14 YAPORA PRATAMA PEKANBARU - M. Abdi Dimas Prayitno; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is that there is a lack of shooting ability of U14 SSB player Yapora Pratama Pekanbaru, this can be seen from various trials and official matches and this is one of the factors causing the defeat. This type of research is a kind of weak research experiment to see the effect of the form of training. The purpose of this study is to see the effect of training in kicking nine balls towards the shooting ability of the U14 SSB player Yapora Pratama Pekanbaru. The populations in this study were all active members in Yapora Pratama Pekanbaru's U14 SSB totaling 38 people. The sampling technique is by using probability sampling, where the number of samples to be taken is 14 people. Data collection techniques obtained from the pre-test and post test. The instrument in this study used the Test of shooting the ball to the target or shooting as a tool to measure shooting ability. The analysis was carried out using the t-test. Based on data analysis and discussion, it can be concluded that there is a significant effect of training kicking nine balls on goal against the shooting ability of the U14 SSB player Yapora Pratama Pekanbaru as evidenced by the Tcount of 7.931 and Ttabel 1.761. Means Tcount> T table. At the level of ɑ = 0.05.Key Words: training kick nine balls, shooting ability